Conocimiento y prácticas de bioseguridad en enfermeras de centro quirúrgico. Hospital General Nuestra Señora Del Rosario Cajabamba - Bermúdez Delfin, Diana Johanna (2021)
This descriptive, correlational research study was carried out in the surgical center service of the General Hospital Nuestra Señora Del Rosario Cajabamba 2018 with the aim of determining the relationship between the level of knowledge and the practice of biosecurity measures in nurses. The sample was 19 nurses. Two instruments were applied: a questionnaire to measure knowledge about biosecurity measures and a checklist on practices in biosecurity measures. The results conclude that; 57.9% of nurses have a medium level of biosafety knowledge, 42.1% a high level, and no nurse has a low level. Regarding the practice of biosecurity measures used by nurses, it was observed that 52.6% of nurses had a medium level of practice, 47.4% was high, and no nurse had a low level. When establishing the relationship between the level of knowledge and the practice of biosafety measures in the 19 nurses who participated in the study, it is observed that 42.1% of nurses have a medium level of knowledge and their level of practice is regular, and the 31.6% of nurses have a high level of knowledge and a good level of practice. In addition, a chi square value of 4.23 is observed with a probability of 0.040 being significant; that is, there is a relationship between the variables